Exploring Teacher’s Practices of Blended ICT in University Mathematics Classroom: A Multicultural Perceptive - G.C., Laxmi (ILAM इलम, 2023)
The purpose of this study is to explore teachers' perspectives and practises of blending information, communication, and Technology (ICT) in mathematics classes at the university level. In addition, this study aims to explore the empowering ways to use blending ICT in teaching mathematics. This study has been conducted using a phenomenological design through an in-depth interview. For in-depth interviews, three mathematics teachers were selected who are teaching graduate level through online modes to explore their experience and practices of blending ICT in their teaching. The data have been analysed by transcribing, coding, categorising, and thematizing. Based on the information provided by the key respondents, various significant findings were obtained: teachers and students are found to be motivated to use ICT tools in the teaching process; ICT can be used as resource tools from many perspectives. The study also explored many physical and psychological problems associated with blending ICT tools in teaching mathematics. There are two ways in which the use of blended ICT in mathematics teaching can be improved: raising ICT awareness and ensuring access to ICT among students and teachers.